Answer:
So your answer is d = -1/4 = -0.250
Explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
6*d-11/2-(2*d-13/2)=0
13
Simplify ——
2
11 13
(6d - ——) - (2d - ——) = 0
2 2
2.1 Subtracting a fraction from a whole
Rewrite the whole as a fraction using 2 as the denominator :
2d 2d • 2
2d = —— = ——————
1 2
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
2.2 Adding up the two equivalent fractions
Add the two equivalent fractions which now have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
2d • 2 - (13) 4d - 13
————————————— = ———————
2 2
11 (4d - 13)
(6d - ——) - ————————— = 0
2 2
11
Simplify ——
2
4.1 Subtracting a fraction from a whole
Rewrite the whole as a fraction using 2 as the denominator :
6d 6d • 2
6d = —— = ——————
1 2
4.2 Adding up the two equivalent fractions
6d • 2 - (11) 12d - 11
————————————— = ————————
2 2
5.1 Adding fractions which have a common denominator
Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:
(12d-11) - ((4d-13)) 8d + 2
———————————————————— = ——————
2 2
6.1 Pull out like factors :
8d + 2 = 2 • (4d + 1)
4d + 1 = 0
4d + 1 = 0
7.1 Solve : 4d+1 = 0
Subtract 1 from both sides of the equation :
4d = -1
Divide both sides of the equation by 4:
d = -1/4 = -0.250